Hand, foot, and mouth disease in an infant - Sandra Caridad Laurencio Vallina; Mileydis Álvarez Caballero; Tania Hernández Lin (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a 9 months of age infant assisted in the emergency room of "José Martí"  Teaching Polyclinic in Santiago de Cuba is presented, due to exanthematic and erythematous lesions in the skin, with bladders around the mouth, as well as in hands, legs and both feet, besides fever.  The mouth, hand and foot disease was diagnosed, keeping in mind the clinic and the increment of this disorder transmitted by the Coxsackie virus in the municipality, reason why he was admitted at home, with medical supervision and followed by the family nurse and physician who indicated the measures for the health control that should be known and applied in the family to decrease the risk of infection.